Nutrients Composition of Some Fodder Tree Leaves Available in Sub-mountainous Region of Himachal Pradesh - Khatta, Vinod; Katoch, B. S. (Indian Forester, 1983)
Ten species of fodder trees from the high rainfall mountainous zone (Palampur) and six species from the hot and humid shivalik zone (Jawalamukhi) were selected for determining the comparative nutritive value, cell-wall and cell-contents. Macro-minerals (Ca & P) and traceminerals (Cu and Zn). The comparison was possible only in five specie. viz siras (Albizzia lebbek), tuni (Cedrela toona), biul (Grewia oppositifolia), Magar (Banbusa arundinacea) and toot (Morus alba). The crade protein (CP) and crude fibre (CF) levels are higher and nitrogen -free-extract (NFE) lower in the samples from high rainfall mountainous zone as compared to those of hot and humid shivalik zone. Similarly the neutral-detergent fibre (NDF) and aciddetergent fibre (ADF) levels are lower and reverse is the case for cell-Content in the samples from the first zone as compared to those of second zone. Exceptino siras (Albizzia lebbek), tuni (Cedrela toona) and dheon (Artocrpus lakoocha) , all the fodder tree leaves were sufficiently rich in copper viz. more than 1 mg/100 g, while all were deficient in zinc viz. less than 5 mg/100 g except toot (Morus alba) On the basis of overall chemichal analysis. Toot (Morus alba) stands first, successively followed by biul (Grewia Oppositifolia) magar (Bambusa arundinacea) and khirk (Celtis australis). All of them were well adaptable for both the zones. Tuni (Cadrela toona) foliage however, has a very good nutritive value excepting deficient in trace-minerals, but its palatability is very poor. Similarly siras (Albizzia lebek)and oee (Albizzia stipulata) are not only nutritionally poorer but also prove some times toxic (fresh growth).